Unexpected Сonnections: Cultural-Historical Psychologyin a Community Mental Health Setting? - Thomas P.B. (Moscow State University of Psychology and Education, 2021)
This paper will reflect on the influence of Vygotsky and Luria in my work as an occupational therapist in the community mental health setting of an ‘Activity Centre’ in the National Health Service, between 1991 and 2001. The paper will discuss a limited study, referencing Vygotsky during that period, with the benefit of hindsight and subsequent developments in the field of cultural-historical psychology. The origi¬nal study raised the questions of what evidence could be found to support the application of Vygotsky’s Zone of Proximal Development (ZPD) with a mixed group of adults in a community setting, and how this process of learning might be assessed and evaluated. At the time, these questions were informed by litera¬ture sources no later than 1998, and learning theory was often absent from professional training in mental healthcare. However, I will propose that some models of practice in mental health — particularly those founded in psycho-analytic group therapy and occupational therapy — could be enhanced by a deeper un-derstanding of Vygotsky’s ZPD, Luria’s model of field research, and the discussion of some less established connections in psychoanalytic praxis.